Evaluation of a regenerated natural meadow in a semi-arid area of Algeria - Abbas K.; Madani T.; M'Hammedi Bouzina M.; Laouar M.; Abdelguerfi A.; Tedjari N. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
A fodder mixture was tested to regenerate a permanent meadow (PR) in the semi arid-area of Sétif (Algeria), on one hectare and was compared to a natural meadow (PN). The PR dry biomass is 1.3 t/ha on average on the year of installation (2005/2006) and 8.22 t/ha the following year. For PN it was 7.0 t/ha the first year and 8.36 t/ha the second year. Then, PR biomass increased strongly the second year to approach that of PN. A comparison between PR and PN regarding floristic composition gives 76% against 46% for grasses, 19% against 26% for legumes and 5% against 28% for the other species, on the first year; and 62% against 84% for grasses, 30% against 11% for legumes and 8% against 5% for the other species, the following year. The floristic composition of the regenerated meadow was clearly improved.
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)